The Role of miR-539 in the Anterior Cingulate Cortex in Chronic Neuropathic Pain. Issue 12 (30th March 2017) - Ding, Mingxia; Shen, Weihong; Hu, Yifeng
Abstract: Objective: This study explored the putative mechanisms of miRNAs in the anterior cingulate cortex (ACC) in modulation of neuropathic pain induced by chronic constriction injury (CCI) of the sciatic nerve. Design and Methods: MiRNA microarray and quantitative real-time polymerase chain reaction (qRT-PCR) were used to examine miRNA expression profile in the ACC after CCI of the sciatic nerve. MiRNA mimics were then used to examine the role of miR-539 in the ACC in modulation of NR2B subunit expression and neuropathic pain in rats. Results: The expression of nine miRNAs was enhanced, and the expression of 12 miRNAs, such as miR-539, was reduced in the ACC after CCI. We confirmed that miR-539 expression was decreased robustly in the contralateral, but mildly in the ipsilateral, ACC. This was associated with enhanced protein levels of NR2B in a similar pattern. Furthermore, administrations of miR-539 mimics into the contralateral ACC, but not the ipsilateral ACC, attenuated CCI-induced mechanical allodynia. This was associated with reduction in protein levels of NR2B in the contralateral ACC. Finally, administrations of Ro25-6981 into the contralateral ACC attenuated the CCI-induced mechanical allodynia to a greater extent than the ipsilateral ACC. Conclusions: Our results suggested that CCI induces lateralized adaptations of NR2B subunit expression in the ACC, which is likely in part contributed by alterations of miR-539 expression, and may promote the regulations of neuropathic pain via NR2B-containing NMDA receptor–mediated neuronal mechanisms.